2000
DOI: 10.1038/sj.bjp.0703068
|View full text |Cite
|
Sign up to set email alerts
|

Urothelium‐derived inhibitory factor(s) influences on detrusor muscle contractility in vitro

Abstract: The function of the bladder urothelium in modulating contractile responses of the underlying detrusor smooth muscle to muscarinic stimulation has been examined in the pig bladder. Saturation curves for [ 3 H]-QNB binding demonstrated a greater muscarinic receptor density in the urothelium than in the detrusor smooth muscle. The presence of an intact urothelium on isolated bladder strips inhibited contractions induced by carbachol but not KCl. Contractions of a urothelium-denuded muscle strip were inhibited in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
231
2
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 237 publications
(258 citation statements)
references
References 17 publications
(18 reference statements)
19
231
2
2
Order By: Relevance
“…Our determination of receptor density closely matches data from receptor binding protocols [Hawthorn et al, 2000;Mans¢eld et al, 2005], with a greater density in the urothelium than in the smooth muscle for pig bladders. The immunoprecipitated M 2 and M 3 receptors accounted for 69% of the total urothelial and 61% of the total muscle receptors.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Our determination of receptor density closely matches data from receptor binding protocols [Hawthorn et al, 2000;Mans¢eld et al, 2005], with a greater density in the urothelium than in the smooth muscle for pig bladders. The immunoprecipitated M 2 and M 3 receptors accounted for 69% of the total urothelial and 61% of the total muscle receptors.…”
Section: Discussionsupporting
confidence: 73%
“…This alludes to a role of bladder urothelium in causing the change in phenotype of detrusor smooth muscle from the M 3 contractile phenotype to either mixed M 2 and M 3 phenotype or the M 2 contractile phenotype, due to the increased density of muscarinic receptors in the urothelium. Inhibition of smooth muscle contraction is induced by functional urothelium, suggesting the presence of a di¡usible inhibitory factor [Hawthorn et al, 2000]. This di¡usible inhibitory factor has yet to be identi¢ed, however, studies in pig and human but not rat bladder strips have suggested that carbachol stimulation of muscarinic urothelial receptors leads to the release of this di¡usible inhibitory factor which can regulate detrusor contractility [Hawthorn et al, 2000;Chess-Williams, 2002;Chaiyaprasithi et al, 2003].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Local mechanisms appear to be involved since spontaneous contractile activity of isolated tissues has been observed (Jiang et al, 2005). In recent years the urothelium and the underlying lamina propria (here abbreviated to U&LP) have been recognized as important regulators of bladder activity, releasing factors that modulate detrusor contraction (Hawthorn et al, 2000, Templeman et al, 2002 and sensory nerve activity (Cockayne et al, 2000). Furthermore, these roles may be clinically relevant since the inhibitory effect these tissues have on detrusor contraction is depressed in the neurogenic overactive bladder (Chess-Williams, 2009), while non-neuronal ATP release from this tissue is enhanced in the bladders of patients with painful bladder (sensory) syndrome (Kumar et al, 2007).…”
Section: Introductionmentioning
confidence: 99%